THE EFFECT OF INDIVIDUALIZATION SRATEGY AND LEARNING STYLE ON STUDENTS’ ACHIEVEMENT IN READING COMPREHENSION AT FACULTY OF TARBIYAH SCIENCE AND TEACHER TRAINING OF STATE ISLAMIC UNIVERSITYNORTH SUMATRA - Yani Lubis (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2018)
The objectives of this study were to examine whether (1) the students’ achievement in reading comprehension taught by Individualization Strategy, (2) the achievement in reading comprehension of the students with introvert learning style if they taught by Individualization strategy higher than extrovert learning style, (3) there is significant effect of Individualization Strategy and Learning Styles on the students’ achievement in reading comprehension. It was an experimental research with factorial design 2x2. The data were analyzed by using two-way ANOVA by using SPSS program. After the data had been calculated, it is found that (1) DRTA and Individualization strategies has affect students’ achievement in reading comprehension (Sig. = 0.026<0.05), students’ achievement in reading comprehension taught by Individualization strategy (76.10). (2) the achievement in reading comprehension of the students with Extrovert learning style is higher than the students with Introvert learning style (83.64>73.80) and (3) there is no interaction between teaching strategies and Learning Style if they combined on the students’ achievement in reading comprehension (Sig. = 0.658 > 0.05).Key Word: Individualization Teaching Strategies; Learning Style; Students’ Achievement